Developing Solutions with Microsoft® InfoPath™ - Halstead, Patrick; Blain, Matthew; Mandava-Teradesai, Vani (Microsoft Press, 2004)
Deliver innovative, XML-based business solutions with a dynamic, easy-to-use front end-faster-with expert guidance, design patterns, and inside insights from two veterans of the Microsoft InfoPath development team.